Volatile Compound Profiling and Quality Assessment of Sweet Fermented High-Amylose Rice: A Comparative GC-MS Analysis with Traditional Glutinous Rice Fermentation - Kamonwan Chucheep; N. Siriwong; Zee Wei Lai; Naree Phanchindawan (Molecules, 2026)
: 3.30 vs. 5.20 μg/mL, representing 36% improvement). Degree of gelatinization analysis validated comparable starch gelatinization (32.5-40.1%) despite different cooking methods, confirming volatile differences arose from rice variety rather than processing. These findings demonstrate high-amylose LPC rice as a promising fermented food substrate offering enhanced nutritional properties and volatile compound profiles through traditional fermentation.
Keywords: GABA and Rice Research; Probiotics and Fermented Foods; Food composition and properties